The effects of going public on firm performance and strategy - Larrain, Borja,Phillips, Gordon M.,Sertsios, Giorgo,Urzúa I., Francisco (Tuck School of Business at Dartmouth], 2021)
We study the effects of going public using a unique panel of firms in 16 European countries for which we observe financial data before and after firms' initial-public-offering (IPO) attempts. We compare firms that complete their IPO with firms that withdraw their IPO. We instrument the going public decision using prior market returns. We find that firm profitability goes up after going public - contrary to previous results in the literature. We also find an post-IPO expansion in the number of subsidiaries and countries in which IPO firms operate. Our results are stronger for firms in financially dependent industries and in countries with higher investor protection consistent with going public relaxing financial constraints and with a stronger impact when agency conflicts are lower. Overall, our results are consistent with going public inducing a shift towards a strategy of commercialization to increase profitability
10.2139/ssrn.3830690
Keywords: Graue Literatur; Selection; Treatment; IPOs; Profitability; Commercialization; Instrumental Variables